Tetranuclear ruthenium(ii) complexes with oligo-oxyethylene linkers as one- and two-photon luminescent tracking non-viral gene vectors. Issue 15 (18th March 2015) - Qiu, Kangqiang; Yu, Bole; Huang, Huaiyi; Zhang, Pingyu; Ji, Liangnian; Chao, Hui
Abstract : Four tetranuclear ruthenium(ii ) complexesRu1–Ru4 based on oligo-oxyethylene and polybenzimidazole have been developed as one- and two-photon luminescent tracking non-viral gene vectors. Abstract : To prolong the observation time, increase the penetration depth and decrease self-absorption and phototoxicity, two-photon luminescent vectors have emerged as promising tools for tracking gene delivery in living cells. Herein, we report four new tetranuclear Ru(ii ) complexes based on oligo-oxyethylene and polybenzimidazole as one- and two- photon luminescent tracking non-viral gene vectors. In such a molecular design, the oligo-oxyethylene, polybenzimidazole and Ru(ii ) polypyridyl complexes were expected to render the vectors with increased cell permeability, biocompatibility, proton buffering capacity and one- and two-photon luminescence. Corresponding DNA interaction studies showed that the ability of the complexes to condense DNA decreased with increasing oligo-oxyethylene lengths. Additionally, all complexes protected DNA. The complexes were investigated as one- and two-photon tracking non-viral gene vectors in living cells and showed proper cellular uptake, good luciferase expression and low cytotoxicity.